SARS-CoV-2 and Streptococcus pneumoniae colonization and disease: an observational study in adults - Calvo-Silveria, Sara; Fernández-Delgado, Lucía; González-Díaz, Aida; España-Bonilla, Rocío; Calatayud, Laura; Niubó, Jordi; Martí, Sara; Domínguez, Ma Ángeles; Càmara, Jordi; Ardanuy, Carmen (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe COVID-19 pandemic has impacted global health and altered respiratory pathogens. While SARS-CoV-2 vaccines have mitigated COVID-19 severity, emerging variants remain challenging. Co-infection of Streptococcus pneumoniae with respiratory viruses is associated with increased disease severity, but its relationship with SARS-CoV-2 remains unclear. This study aims to analyze their co-occurrence, focusing on disease progression, colonization rates and clinical outcomes.MethodsTo this end, three approaches were used. First, a laboratory-based analysis of invasive pneumococcal disease (IPD) in adults (2019-2023). Second, a retrospective analysis of COVID-19 clinical cases with pneumococcal isolates (March,2020–December,2023), including clinical and microbiological data such as patients’ comorbidities, episode severity, serotypes and resistance genes. Third, a retrospective analysis to assess pneumococcal colonization in SARS-CoV-2 positive nasopharyngeal samples (May-October 2023; dual-target RT-PCR). WGS and bioinformatics were performed on both bacterial (serotyping and resistance analysis) and viral genomes (lineage determination). Statistical comparisons (Chi-square, Fisher’s test), with significance set at p<0.05.ResultsFirst, IPD incidence declined during the COVID-19 pandemic, with cases dropping by 70% in both age groups (18–64 and >64) from 2019 to 2021 and rebounding after 2021, concomitant with the relaxation of non-pharmaceutical measures, especially among older adults. Pneumococcal serotype distribution remained stable with dominance of serotypes 3 and 8. Serotype 12F disappeared during the lockdown and re-emerged in 2023 as a multidrug-resistant sub-lineage through multi-fragment recombination, derived from the former GPSC26. Second, SARS-CoV-2 and pneumococcal co-infection occurred in 66 hospitalized patients, mainly by serotype 3 (15%), with resistance to macrolides (26.3%) and tetracycline (22.8%). Third, pneumococcal colonization in SARS-CoV-2-infected patients was low (2.8%), especially in older adults (>64 years; 1.5%), with slightly higher rates in severe cases (4.7% vs 2.5%; p=0.404; IC95% 0.13-3.05) and young adults (4.8% vs 1.5%; p=0.04; IC95% 0.92-15.21). Compared to colonized patients, those with co-infection had more comorbidities, more severe clinical presentations, higher hospitalization rates and lower vaccination rates.DiscussionThis study highlights how non-pharmaceutical measures disrupt S. pneumoniae dynamics. Although pneumococcal colonization in SARS-CoV-2 patients appears to be infrequent, our data suggest an increase in disease severity. Then, vaccination programs and their monitoring remain critical in the prevention of respiratory infections.